Cash transfer and labor supply: effects of a large-scale emergency program in Brazil - Megale, Rodrigo Ulian (2024)
Cash transfer programs typically have null or minor effects on beneficiaries\' labor supply. This study adds to the literature by examining a large-scale income transfer program in Brazil during the COVID-19 pandemic: the Auxílio Emergencial (AE). This scenario could arguably be most conducive for beneficiaries to exit the labor market as a means of pandemic protection. Our findings for the aggregate labor force align with the literature consistently showing no effect of the transfer on the chance of being active in the labor market. Yet, when disaggregating these effects for those initially active and inactive in the labor market during the baseline period, it was identified offsetting effects for each group, leading to the overall null effect. The benefit positively impacted the inactive, first towards informality or unemployment, but positively towards formality after 4 months of exposure. This suggests that those outside the labor market might have used the aid to acquire tools for informal work or to seek better jobs in the short term. Heterogeneous effect analysis reveals this effect is even stronger for minorities, such as women, non-whites, and residents of the North and Northeast regions. Conversely, the Auxílio Emergencial reduced the labor supply of those who were already active in the baseline period, particularly among informal workers or the unemployed. This effect is also more pronounced for women, likely linked to single mothers who received double the benefit, and for whites, probably due to the higher total income associated with this group. Thus, the program seems to provide some protection against the virus for this segment of the population, which is seem as a \"positive\"result in this context.